2018
DOI: 10.1029/2018jg004554
|View full text |Cite
|
Sign up to set email alerts
|

B Vitamins and Their Congeners as Potential Drivers of Microbial Community Composition in an Oligotrophic Marine Ecosystem

Abstract: Determining the factors that influence marine microbial growth and community structure are critical for the understanding of global carbon cycling. Since the early twentieth century, it has been known that B vitamins play an important role in phytoplankton community dynamics. Limited oceanic dissolved B vitamin distributions indicate that these important coenzymes are present at picomolar levels, which could be too low to support maximal phytoplankton growth, and vast regions of the ocean exist where they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 110 publications
(243 reference statements)
12
50
3
Order By: Relevance
“…Some of the putatively auxotrophic organisms actually encode parts of their vitamin biosynthesis pathways, and therefore may depend on the uptake of a precursor rather than of the vitamin itself (Supplementary text, Supplementary Fig.s 7a-d). Our results, together with experimental observations of vitamin limitation in laboratory cultures and in nature [58,61,67], and of shifts in the capacity of marine communities to produce vitamins [68], argue for an important role of vitamins or their precursors and their exchange between organisms in shaping marine microbial communities. Supplementary Fig.…”
Section: Many Bacteria Need "To Shop" For Their Vitaminssupporting
confidence: 52%
“…Some of the putatively auxotrophic organisms actually encode parts of their vitamin biosynthesis pathways, and therefore may depend on the uptake of a precursor rather than of the vitamin itself (Supplementary text, Supplementary Fig.s 7a-d). Our results, together with experimental observations of vitamin limitation in laboratory cultures and in nature [58,61,67], and of shifts in the capacity of marine communities to produce vitamins [68], argue for an important role of vitamins or their precursors and their exchange between organisms in shaping marine microbial communities. Supplementary Fig.…”
Section: Many Bacteria Need "To Shop" For Their Vitaminssupporting
confidence: 52%
“…4c). Unfortunately we lack B1 measurements in this study, but, according to previous field studies in other oceanographic regions, a similar pattern to that observed for B12 can be expected (Cohen et al, 2017;Sañudo-Wilhelmy et al, 2012;Suffridge et al, 2018). The overall low and stable concentration of B12 at both sampling locations is consistent with the expected high turnover time of this compound in productive, well-lit waters (Bertrand et al, 2015), due to both biological uptake (Koch et al, 2012;Taylor and Sullivan, 2008) and photochemical degradation (Carlucci et al, 1969;Juzeniene and Nizauskaite, 2013;Juzeniene et al, 2015).…”
Section: Positive Responses To Vitamin B1 and B12 Amendmentssupporting
confidence: 85%
“…Some of the putatively auxotrophic organisms actually encode parts of their vitamin biosynthesis pathways, and therefore may depend on the uptake of a precursor rather than of the vitamin itself (Supplementary text, Supplementary Fig.s 7a-d). Our results, together with experimental observations of vitamin limitation in laboratory cultures and in nature (58,61,67), and of shifts in the capacity of marine communities to produce vitamins (68), argue for an important role of vitamins or their precursors and their exchange between organisms in shaping marine microbial communities.…”
Section: Many Bacteria Need "To Shop" For Their Vitaminssupporting
confidence: 52%
“…They are metabolically expensive to produce as they often need several enzymes (e.g. about 20 for vitamin B12) (60), and their availability in the dissolved extracellular pools is extremely limited across all aquatic ecosystems (61,62). Some phytoplankton are known to require exogenous vitamins from co-occurring heterotrophic bacteria, and indeed vitamin B12 may be a co-limiting micro-nutrient for primary productivity, e.g.…”
Section: Many Bacteria Need "To Shop" For Their Vitaminsmentioning
confidence: 99%